Work disability in systemic sclerosis – What is known? - A. A. Klimenko; E. P. Mikheeva; N. A. Shostak; N. A. Demidova (Научно-практическая ревматология)
The medical and social significance of systemic sclerosis (SSc) is high. The progressive disease has a significant impact on the functional status, work participation and leads to early disability in patients of working age. The article presents data on the prevalence of work disability in patients with SSc in comparison with other rheumatic diseases, the frequency of separation from work and work transitions due to the problems connected with SSc, the socio-economic burden of SSc in different countries. The article specifies the components of the disease which affect the ability to work, the main approaches to quantify the indicators of working ability, describes the instruments most commonly used for this purpose. The data of various authors on working ability measurement and predictors of work disability in patients with SSc are presented.